Pinky and Rex - Howe, James, 1946-; Sweet, Melissa, 1956- (New York : Atheneum, 1990)
Rex and her best friend Pinky, each the proud possessor of twenty-seven stuffed animals or dinosaurs, find their visit to the museum and its gift shop complicated by Pinky's little sister Amanda.
Keywords: Museums -- Fiction; Friendship -- Fiction; Siblings -- Fiction; Toys -- Fiction